New records of Phlebotomus (Transphlebotomus) mascittii Grassi, 1908 in northern Rhineland-Palatinate (Diptera, Psychodidae, Phlebotominae) - Andreas Krüger; Anke Crecelius; Denise Fischer; Ralf M. Hagen (Contributions to Entomology)
In the three consecutive years of 2022–2024, three female specimens of the phlebotomine sandfly Phlebotomus mascittii were trapped in two locations in the vicinity of Coblenz, western Germany. These records slightly expand the distribution limits of the species in the Federal State of Rhineland-Palatinate to the north, at latitudes 50°18'N and 50°15'N, respectively, and represent the second northernmost Palearctic sandfly locations so far.